If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + 4x = 2(11 + 4x) 11 + 4x = (11 * 2 + 4x * 2) 11 + 4x = (22 + 8x) Solving 11 + 4x = 22 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 11 + 4x + -8x = 22 + 8x + -8x Combine like terms: 4x + -8x = -4x 11 + -4x = 22 + 8x + -8x Combine like terms: 8x + -8x = 0 11 + -4x = 22 + 0 11 + -4x = 22 Add '-11' to each side of the equation. 11 + -11 + -4x = 22 + -11 Combine like terms: 11 + -11 = 0 0 + -4x = 22 + -11 -4x = 22 + -11 Combine like terms: 22 + -11 = 11 -4x = 11 Divide each side by '-4'. x = -2.75 Simplifying x = -2.75
| 0.3-2=7 | | 3x+2(x-1)=2 | | 4x+12-3x=19 | | 4x^4-4x^3-25x^2+x+6=0 | | 5/9x-1/3=1/5 | | 18+2=44 | | 3x-3+9=5x-7-3x | | 9x+3=7x+8 | | 6p+7q=39 | | (2x+66)=(8x+6) | | 7v+10=8v+v | | m^2=-3m+18 | | -21=0.5c-11 | | 17+w=94 | | p+.3p=.6 | | x^4-2x^3+x^2-4=0 | | 2x^2+9x=6x+20 | | 0.08(3v-4)=0.4(v-4) | | 3(v+8)-10v=-7v-42 | | 4+0.6x=16 | | 20x-6=40x+6 | | -78+n=-133 | | 2x+42+1+3x-31=180 | | -6(-6+5x)-6(x-7)=x+3+7-3x | | x^3-4x^3+3x=0 | | 4r+1=11a+8 | | 3-.22222222b=.33333333b-7 | | 6y+2x=32 | | (7+2x)=30+7(x-1) | | 2x(42)+1+3x-31=180 | | Y=9x-9+9x+16+6x+3 | | x+122=76 |